14(x-6)+4x=6(3t+2)-11

Simple and best practice solution for 14(x-6)+4x=6(3t+2)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14(x-6)+4x=6(3t+2)-11 equation:


Simplifying
14(x + -6) + 4x = 6(3t + 2) + -11

Reorder the terms:
14(-6 + x) + 4x = 6(3t + 2) + -11
(-6 * 14 + x * 14) + 4x = 6(3t + 2) + -11
(-84 + 14x) + 4x = 6(3t + 2) + -11

Combine like terms: 14x + 4x = 18x
-84 + 18x = 6(3t + 2) + -11

Reorder the terms:
-84 + 18x = 6(2 + 3t) + -11
-84 + 18x = (2 * 6 + 3t * 6) + -11
-84 + 18x = (12 + 18t) + -11

Reorder the terms:
-84 + 18x = 12 + -11 + 18t

Combine like terms: 12 + -11 = 1
-84 + 18x = 1 + 18t

Solving
-84 + 18x = 1 + 18t

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '84' to each side of the equation.
-84 + 84 + 18x = 1 + 84 + 18t

Combine like terms: -84 + 84 = 0
0 + 18x = 1 + 84 + 18t
18x = 1 + 84 + 18t

Combine like terms: 1 + 84 = 85
18x = 85 + 18t

Divide each side by '18'.
x = 4.722222222 + t

Simplifying
x = 4.722222222 + t

See similar equations:

| a(x-b)=c | | -3x^2-9x+3=0 | | 8n^2+n+11=0 | | -(4x+1)-(-3x-5)=-3 | | -(4x+1)-(-3y-5)=-3 | | 8n^2+n=-11 | | 0.5x-3=17 | | 5(x^2-3)=5 | | 8y+8=64 | | 6r^2-9=3 | | G-5=-9 | | 2+-6=y | | a^2-10=50 | | 1x+5=13 | | -10x^2=-360 | | x-8.1=-6.9 | | x+33=24 | | n^2-3=46 | | 9y-1=80 | | 10x-2=-72 | | 10x+15=95 | | 5x+32=x | | n^2=46 | | 5+2h=20 | | -72-3(-9-4)=3(-9-4)+6 | | 5y-5=10 | | 8x-3(x-4)=3(x-4)+6 | | 2y-7=9 | | y=4x+3whatisy | | 3x-2(2+5)=2(x+3)-8 | | 10x+14=34 | | -5x+5=10 |

Equations solver categories